Resting the Case: The Role of Sex on the Affective and Cognitive Domain in Mathematics Learning Among Pre-Service Teachers - Cristine Pearl Morales; Justin L. Tejada; Ana Marie Timan; Mark Donnel Viernes (CV. Samuel Manurung and Co, 2025)
With the world’s education system evolving to be more inclusive than in previous centuries, recent literature suggests that gender disparity in mathematics is minimal and insignificant – a contradictory notion in the last hundred years. This descriptive-comparative study aimed to determine whether gender still plays a role in the established link between affective and cognitive domains of learning mathematics. The study focused on adult learners, specifically future teachers – a female-dominated profession. One hundred sixty-five pre-service teachers (45% male, 55% female) from a Teacher Education Institution in the western Philippines participated in the study. The research used statistical methods such as frequency, percentages, one-way and two-way ANOVA to address the research questions. The results revealed that most pre-service teachers have low confidence levels, high anxiety levels, and low math performance. There is a significant difference on math performance when grouped according to levels of anxiety, but not on sex and levels of confidence. We also found no interaction effect between sex and levels of anxiety to math performance. Similarly, the interaction of sex and levels of confidence to math performance is not significant. The study suggests that Teacher Education Institutions (TEIs) and the Department of Education review and evaluate their curriculum for content mastery. TEIs are also advised to address stereotype threats to maintain balance and prevent gender disparities among future teachers